2011
DOI: 10.3168/jds.2010-3280
|View full text |Cite
|
Sign up to set email alerts
|

Frozen yogurt with added inulin and isomalt

Abstract: The objective of this study was to produce a frozen yogurt containing low fat and no added sugar. Samples containing 5% polydextrose, 0.065% aspartame and acesulfame-K mixture, and different levels of inulin and isomalt (5.0, 6.5, and 8.0%) were produced at pilot scale and analyzed for their physical and chemical properties including proximate composition, viscosity, acidity, overrun, melting rate, heat shock stability, as well as sensory characteristics, and viability of lactic acid bacteria. With the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 24 publications
2
35
0
6
Order By: Relevance
“…For the taste attribute, the standard formulation (F1) showed greater acceptance (p<0.05) than F5, without statistical difference from the others, whose results were also verified by Aplevlicz and Dias (2010 is slightly sweet, representing only 10% of the sweetness of sucrose (ISIK et al, 2011), which was reduced in the formulations of the present research. Despite the lower evaluation for appearance and taste attributes of F5, issues of global acceptance and purchase intention received positive results, since the judges did not detect differences between the standard samples and those with inulin (p>0.05).…”
Section: Sensorial Analysissupporting
confidence: 72%
See 2 more Smart Citations
“…For the taste attribute, the standard formulation (F1) showed greater acceptance (p<0.05) than F5, without statistical difference from the others, whose results were also verified by Aplevlicz and Dias (2010 is slightly sweet, representing only 10% of the sweetness of sucrose (ISIK et al, 2011), which was reduced in the formulations of the present research. Despite the lower evaluation for appearance and taste attributes of F5, issues of global acceptance and purchase intention received positive results, since the judges did not detect differences between the standard samples and those with inulin (p>0.05).…”
Section: Sensorial Analysissupporting
confidence: 72%
“…Among these there are products with low calorie and fiber enriched using ingredients such as fructooligosaccharides (FOS) and inulin. These products present many advantages, because they can replace, mainly, sugar and fat in food products (FRANCK, 2002;ISIK et al, 2011;MANTZOURIDOU et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar values were observed by Sivieri and Oliveira (2002) in their sensory evaluation of dairy beverages containing fat substitutes. In this study, the addition of inulin did not influence the sensory acceptance of the beverage because no significant differences were observed between formulations PI and C. Similarly, Isik et al (2011) observed that the addition of inulin did not affect the sensory acceptance of frozen yogurt.…”
Section: Sensory Analysismentioning
confidence: 58%
“…Corte (2008) found 2.2 × 10 8 CFU/g to 1.2 × 10 9 CFU/g lactic bacteria in frozen yogurt made from cow milk yogurt supplemented with prebiotic (inulin), calcium caseinate and probiotics. Isik et al, (2011) found a count of 8 × 10 8 CFU/g in cow milk yogurt fortified with inulin and isomalt. Thus, it can be seen that frozen yogurt prepared from sheep milk yoghurt powder manufactured by a dehydration process, retained a count of 2 × 10 7 CFU/g.…”
Section: Frozen Yogurtmentioning
confidence: 99%